2019
DOI: 10.3390/f10121144
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Ozone on Forest Trees in An Integrative Perspective: Are Foliar Visible Symptoms Suitable Predictors for Growth Reduction? A Critical Review

Abstract: Plant growth reduction (GR) is the most widely accepted damage parameter to assess the sensitivity of trees to tropospheric ozone (O3) pollution since it integrates different physiological processes leading to loss of photosynthetic activity and distraction of metabolic resources from growth to defense, repair, and recovery pathways. Because of the intrinsic difficulty to assess the actual O3 risk assessment for forests in field conditions, foliar visible symptoms (FVS) induced by O3 have been proposed as a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 106 publications
1
10
0
Order By: Relevance
“…That indicates in general invasive species had higher foliar injury rates under O 3 stress. Given that the degree of foliar injury is closely related with photosynthesis (Marzuoli et al, 2019; Vainonen & Kangasjärvi, 2015), the most likely explanation for the higher growth suppression of invasive species than of native species is the greater photosynthesis suppression due to higher foliar injury in invasive species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That indicates in general invasive species had higher foliar injury rates under O 3 stress. Given that the degree of foliar injury is closely related with photosynthesis (Marzuoli et al, 2019; Vainonen & Kangasjärvi, 2015), the most likely explanation for the higher growth suppression of invasive species than of native species is the greater photosynthesis suppression due to higher foliar injury in invasive species.…”
Section: Discussionmentioning
confidence: 99%
“…Such injuries often appear as chlorosis, necrosis, spots and bronzing (Agathokleous et al, 2020). Some studies suggested that visible foliar injury could be associated with not only plant susceptibility (Bergmann et al, 2017; Davison & Barnes, 1998; Li et al, 2016) but also negative impacts on fitness traits (Marzuoli et al, 2019). In agricultural ecosystems, the influence of elevated O 3 on crop species has received much attention and is well understood, especially the effect on yield reduction (Ainsworth, 2017; Tai et al, 2014; Wilkinson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While it is difficult to distinguish whether chlorosis and necrosis are induced by O 3 or normal senescence in the field, a characteristic of O 3 -induced symptoms is that they usually occur on interveinal areas of the upper leaf surface only and older leaves show the most symptoms. Species-specific visible injuries have been widely found in nature ( 10 , 35 37 ), although evidence for the relationship between O 3 -induced visible injuries and damage is contradictory and uncertain especially for forest trees ( 38 ). Visible injuries may be associated with negative impacts on fitness traits [e.g., the reduction of carbon (C) assimilation/allocation limits growth and seed production, making the species uncompetitive] ( 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…Species-specific visible injuries have been widely found in nature ( 10 , 35 37 ), although evidence for the relationship between O 3 -induced visible injuries and damage is contradictory and uncertain especially for forest trees ( 38 ). Visible injuries may be associated with negative impacts on fitness traits [e.g., the reduction of carbon (C) assimilation/allocation limits growth and seed production, making the species uncompetitive] ( 38 ). Little is known, however, about the relationship between short-term phenomena such as visible foliar injury and longer-term processes affecting plant-community structure and ecosystem biodiversity ( 5 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the review paper by Marzuoli et al [6] analysed the relationships between visible foliar symptoms and plant growth reduction based on the available literature on forest tree species exposed to ozone in different experimental systems. The authors concluded that the appearance of visible injuries and negative growth responses are consequences of separate physiological processes such as various compensatory, detoxification and repair processes, increased respiration, defoliation and closure of stomata, leading to ozone avoidance.…”
mentioning
confidence: 99%